Exercise-Based Interventions Aimed at Improving Balance in Children with Autism Spectrum Disorder: A Meta-Analysis. Issue 1 (February 2022) - Djordjević, Mirjana; Memisevic, Haris; Potic, Srecko; Djuric, Uros
Children with Autism Spectrum Disorder (ASD) often have deficits in motor skills, especially balance. This article presents a meta-analytic review of 15 intervention studies that aimed to improve balance in children and adolescents with ASD. Across these studies, there were 195 participants with ASD for whom pre-intervention and post-intervention balance scores were available. We measured the standardized mean difference (Hedges' g) between their pre-intervention and post-intervention balance scores and found a large, positive effect from these balance interventions (standardized mean difference—1.82 (95% CI [1.34, 2.29]). Various balance intervention procedures were shown to be very efficacious for children and adolescents with ASD. Clearly, balance is a motor skill that is very susceptible to intervention efforts. We also provided recommendations to researchers regarding what information to include when conducting intervention studies.